Relationship between Quality of Life and Life Style Health Promotion Behaviors in the Elderly - Babak Moeini; Forouzan Rezapor Shakolaei; Tahereh Etesami Frad; Ghodratolah Roshanaei; Hamid Abasi (Hamadan University of Medical Sciences, 2021)
Aims: Elderly is an important period of human life, and the elderly population in Iran is increasing. Therefore, the present study was aimed to investigate the relationship between quality and lifestyle health promotion behaviors among the elderly in Hamadan, 2015. Instrument & Methods: This cross-sectional study was conducted on 230 retired elderly over 60 years selected by cluster sampling method in Hamadan retirement centers. A standard questionnaire for quality of life and lifestyle was used to collect data. Data were analyzed using SPSS-16 software, chi-square, and correlation analysis. The significance level was considered 5%. Findings: Lifestyle in the elderly was undesirable (61.3%), and 38.7% had a moderate quality of life. Physical functioning was the most undesirable aspect of lifestyle, and physical activity was the most undesirable aspect of quality of life. The results of the Chi-squared test showed two significant relationships between lifestyle status and gender as well as the quality of life with gender (p<0.05). The mean of lifestyle and quality of life were significantly different between marital variables (p<0.05). The results showed a positive correlation between lifestyle scores and quality of life (r=0.479, p<0.001). Conclusion: According to an undesirable lifestyle and moderate quality of life in the elderly, it is recommended that interventions be made to increase lifestyle and quality of life, especially in physical functioning, exercise, and physical activity in the elderly.